Predatory spider fauna in fruit crops of Punjab, India along with new records - SINGH, SANDEEP; SEKHAR, RESHMI; K, SUNIL JOSE (The Indian Journal of Agricultural Sciences, 2020)
Spiders are important predatory organisms in the orchards. Keeping in view their role in the natural biological control, the present studies were conducted from May 2012 to October 2019 in orchards belonging to 21 fruit crops, viz. apple (Malus sp.), amla (Phyllanthus emblica), citrus (Citrus spp.), banana (Musa spp.), ber (Zizyphus mauritiana), fig (Ficus carica), grapes (Vitis vinifera), guava (Psidium guajava), jamun (Syzygium cumini), litchi (Litchi chinensis), loquat (Eriobotrya japonica), mango (Mangifera indica), olive (Olea europaea), papaya (Carica papaya), peach (Prunus persica), pear (Pyrus communis), plum (Prunus domestica), pomegranate (Punica granatum), phalsa (Grewia asiatica), rasbhari (Physalis peruviana) and sapota (Manilkara zapota) in 13 districts of the Punjab, India, with an objective to record the prevalence of different families of spider fauna. The study revealed the presence of several predatory spiders involved in controlling various insect-pests of fruit crops. The 43 species of spiders belonging to 23 genera and 13 families were recorded during the study. Families like Salticidae, Araneidae and Oxyopidae exhibited more diversity. Salticidae family showed maximum diversity. High genetic diversity was found in Salticidae, Araneidae, Oxyopidae and Tetragnathidae. Study highlights the importance of protecting natural predators in controlling the insect pests in orchards. Epeus flavobilineatus Doleschall, Epocilla calcarata (Karsch) (Family: Salticidae); Gasteracantha cancriformis (Linnaeus) and Neoscona punctigera (Doleschall) (Family Araneidae) are new species records for India.